Comparative Safety and Efficacy of Eight Antithrombotic Regimens for Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention - Liang, Bo; Zhu, Yong-Chun; Gu, Ning (Frontiers in Cardiovascular Medicine, 2022)
Background Antithrombotic therapy for patients with atrial fibrillation undergoing percutaneous coronary intervention is facing major treatment problems in clinical practice. Methods We firstly conducted a Bayesian network meta-analysis to study the safety and efficacy of different antithrombotic regimens. Only randomized controlled trials from PubMed, Web of Science, Cochrane Central Register of Controlled Trials, Embase, and China National Knowledge Infrastructure were included in our study. The Bayesian random-effects model was used in this study. The primary safety and efficacy outcomes were major bleeding according to the criteria of Thrombolysis In Myocardial Infarction (TIMI) and trial-defined major adverse cardiovascular events, respectively. The secondary safety outcomes were combined TIMI major and minor bleeding, trial-defined primary bleeding events, and intracranial hemorrhage. The secondary efficacy outcomes were all-cause or cardiovascular mortality, myocardial infarction, stroke, stent thrombosis, and hospitalization. Results Total of 11,532 patients from the five randomized controlled trials were analyzed, of whom 8,426 were male. Compared with vitamin K antagonist (VKA) plus P2Y12 inhibitor, the odds ratios (95% credible intervals) for TIMI major bleeding were 1.70 (0.77–3.80) for VKA plus dual antiplatelet therapy (DAPT), 1.20 (0.30–4.60) for rivaroxaban plus P2Y12 inhibitor, 1.00 (0.25–3.90) for rivaroxaban plus DAPT, 0.76 (0.21–2.80) for dabigatran plus P2Y12 inhibitor, 0.71 (0.25–2.10) for apixaban plus P2Y12 inhibitor, 1.40 (0.52–3.80) for apixaban plus DAPT, and 1.00 (0.27–4.00) for edoxaban plus P2Y12 inhibitor. For trial-defined major adverse cardiovascular events, compared with VKA plus P2Y12 inhibitor, the odds ratios (95% credible intervals) were 1.10 (0.61–2.00) for VKA plus DAPT, 1.20 (0.45–3.70) for rivaroxaban plus P2Y12 inhibitor, 1.10 (0.38–3.20) for rivaroxaban plus DAPT, 1.10 (0.43–3.10) for dabigatran plus P2Y12 inhibitor, 1.00 (0.47–2.20) for apixaban plus P2Y12 inhibitor, 0.99 (0.46–2.20) for apixaban plus DAPT, and 1.20 (0.43–3.40) for edoxaban plus P2Y12 inhibitor. Apixaban plus P2Y12 inhibitor was the highest-ranking of safety outcomes and VKA plus P2Y12 inhibitor was the highest-ranking of efficacy outcomes other than trial-defined major adverse cardiovascular events. Conclusion Apixaban plus P2Y12 inhibitor seems to be linked with fewer bleeding complications while retaining antithrombotic efficacy. Moreover, for most efficacy indicators, the ranking of VKA plus P2Y12 inhibitor is still very high. Systematic Review Registration [www.crd.york.ac.uk/prospero/], identifier [CRD42020149894].